EXPERIMENTAL STUDIES OF CLAY MINERAL OCCURRENCE - Manning D.A.C. (My University, 2002)
Fundamental controls on the occurrence and distribution of clay minerals in sedimentary rocks are determined by the application of experimental data relating to their thermodynamic stabilities and the kinetics of clay reactions. The thermodynamic properties of individual representatives of the major clay-mineral groups (kaolin, illite, smectite, chlorite) and polymorphs (kaolinite, dickite, nacrite, halloysite) have been determined mainly from synthesis experiments but also from solubility determinations and calorimetric investigations of natural and synthetic clays. In all cases, mineral starting materials need to be fully characterized to quantify impurities and heterogeneities at a molecular scale. In synthesis and solubility experiments, analysis of the fluid composition is integrated ideally with detailed high-resolution mineralogical analysis of solid experimental products. It is clear from many studies that kinetic factors control both the natural occurrence of clay minerals and the results of synthesis experiments, and this can lead to controversy in the interpretation of experimental data. Recent experimental work on clay-mineral reactions has been undertaken under conditions of pressure and temperature that either match the saturated vapour pressure curve for aqueous solutions, under autoclave conditions, or are at elevated pressure controlled independently of temperature. This review explains the principles involved in experimental design and their limitations, and provides signposts to key studies of clay stability.